A balanced ABS system: Stakeholder perception on ABS goals. (23rd January 2020) - Sirakaya, Aysegul
Abstract: The current perception regarding the implementation of the Nagoya Protocol is that the national implementations bring complexities for both the provider countries and users of genetic resources (GR) which result in less willingness to access GR. Users frequently face non‐compliance penalties or public notoriety due to the lack of clarity of access and benefit‐sharing (ABS) obligations. Less access would inevitably result in fewer benefits shared and this vicious cycle would jeopardise the success of the entirety of the ABS system. Therefore, there is an apparent need for a methodology in regulating ABS models in a way that is supportive for both the provider countries and users. This article serves as the introductory part of a comprehensive study on creating a methodology for mutually supportive ABS systems for users and providers by introducing international ABS goals and the stakeholders' (both users and providers) perceptions thereof.